Supporting Leadership Development: An Examination of High School Principals' Efforts to Develop Leaders' Personal Capacities. (August 2016) - Huggins, Kristin Shawn; Klar, Hans W.; Hammonds, Hattie L.; Buskey, Frederick C.
In this article, we report findings from an exploratory, qualitative study in which we used a constructivist lens to examine how two high school principals endeavored to develop the personal capacities of teachers and other leaders in their schools. We collected data from semistructured interviews with the principals and three other leaders from each of their respective schools. Through our findings, we illustrate the varying degree to which each principal viewed the leaders' existing capacities, structured their leadership learning opportunities, guided their reflections, and assessed their learning in the context of leadership practice. An important finding was that the way the principals viewed leadership development and saw other leaders as learners themselves appeared to influence the way they developed other leaders' personal capacities.